Dairy marketing chains analysis: the case of Shashemane, Hawassa and Dale District’s milk shed, Southern Ethiopia - Somano, W. (Haramaya University, 2008)
The study was initiated with the objectives of analyzing dairy marketing chains in the Hawassa, Shashemane and Yergalem milk shed in southern Ethiopia. The milk shed encompasses Hawassa, Shashemane and Yergalem towns. Milk and butter were the two most important dairy products marketed in the areas. Data came from 180 dairy producing households, 97 butter traders, and 81 milk traders. The Heckman two-stage econometric estimation procedure was employed to identify factors that determine milk market participation decision and milk sale volume of the farm household in the area. The first step of the Heckman two stages procedures results showed that dairy household milk market entry decision was strongly and significantly affected by age of the household head, family size, education level, experience in dairy production, number of cross breed milking cows owned and distance from milk market center. In addition, the second stage estimation result revealed that marketable milk volume was found to be strongly and significantly affected by the number of cross breed milking cows owned, family size, age squared and annual non-dairy income source of sampled dairy household. Eighty five percent of sampled dairy household were identified to be milk market participants and about 65% of milk produced by sampled household was supplied to market. Dairy producers, retailers, farmer traders, ierate traders, dairy producers’ cooperatives and semi-wholesale were found to be important milk and butter market intermediaries of the milk shed. The crossbreed and local breed dairy farm owner are respectively 67.4% and 32.6%. The S-C-P model identified that the markets for milk and butter in the study area was non-competitive type. The highest and the lowest net profit/lit in milk marketing respectively obtained by dairy producers and milk semi-wholesaler. In butter market, butter retailers enjoyed the highest net profit. Generally, milk and butter market in the study area seemed to be inefficient and underdeveloped. Thus, dairy development interventions should be aimed at addressing both dairy production technological gaps and marketing problems. The study further suggested that dairy processing industries formation, dairy producers and trader cooperatives, and improving access to services should receive due attention in order to improve dairy production in general and dairy marketing in particular.